Strategi Pengembangan Ekonomi Kreatif Untuk Menumbuhkan UMKM di Desa Bila Kabupaten Wajo - Andi Yuniarti; Andi Nurwana; Aldi Setiawan (YP-SDI Lamaddukelleng, 2024)
The development of Micro, Small, and Medium Enterprises (MSME) in rural areas is crucial for enhancing local economic welfare and promoting social sustainability. This article explores the role of creative economy socialization as a strategy to grow MSME in rural areas. Creative economy socialization aims to introduce innovative business concepts and practices, including creative marketing techniques, product design, and the use of digital technology. By educating MSME actors about the potential and benefits of the creative economy, the article demonstrates how creativity and innovation can drive product diversification, improve competitiveness, and expand market access. The study identifies various effective socialization methods, such as training, workshops, and mentoring, and assesses their impact on MSME actors' ability to implement creative ideas in their businesses. Findings indicate that creative economy socialization enhances MSME actors' skills and knowledge, contributing to business growth and local economic strengthening. The article provides recommendations for developing more targeted and sustainable socialization programs to strengthen the MSME ecosystem in rural areas and promote inclusive economic growth.